Nature loves to hide : quantum physics and reality, a western perspective - Malin, Shimon, 1937-
It is naturally important for any of us to have a correct view of the universe we are in. Having realized that the Newtonian world-view is untenable, this book joins others that are searching for an alternative world-view. It is unique in using quantum physics to promote this search. One aim of the book is to present a lucid exposition of quantum mechanics in terms accessible to the general reader. Another aim is to show that realism (the belief that the outside world exists "from its own side" regardless of acts of consciousness) and locality (the belief that nothing moves faster than light).